Computational investigation of torque on spiral bevel gears - Rapley, Steve (2009)
This thesis describes the development of a numerical modelling strategy for simulating the flow around a shrouded spiral bevel gear. The strategy is then applied to a series of parametric variations of key shroud parameters. The shroud and gear in question are generic, although based upon those employed in the internal gear box of a Rolls-Royce aeroengine. The need to shroud the gear comes from the fact that a spiral bevel gear, when rotated, acts like a fan. Work is done by the gear to move the surrounding fluid, usually air with oil particles suspended in it, which creates a parasitic loss, referred to as the windage power loss. The work within this thesis is part of a larger project which has investigated how windage power loss can be affected by geometric features of gears and shrouds. This is important as for large diameter (>200mm) bevel gears running at high speeds (>10,000 RPM) the windage power loss forms a substantial part of the total power loss.